Potential applications of lignin and its derivatives from lignocellulosic biomass – a review - Md Salleh, Madihah; Mohd Noor, Rohaya; Yahya, Adibah; Abd-Aziz, Suraini; Hussin, Huszalina (Penerbit Universiti Teknologi Malaysia, 2023)
Lignin is the second most abundant component of lignocellulose biomass after cellulose with annual production of 70 million tons. Lignin constitutes between 15 to 40 percent of its dry weight, with varying composition in woody plants such as softwood (18-25%) and hardwood (27-33%), and non-woody plant such as grass (17-24%). The polyphenolic polymer is made up of three monolignols such as coniferyl alcohol, sinapyl alcohol, andp-coumaryl alcohol that later forms an aromatic structure consisting of guaiacyl, syringyl, and p-hydroxyphenyl. The highly branched three-dimensional structure is both complex and recalcitrant, hence making its utilization difficult. However, the polymeric lignin can be extracted by various methods such as physical, chemical and biological. The extracted lignin has high potential to be converted into monomeric aromatic derivatives that could serve as a building block for chemical synthesis, biomaterials, bio-oils, wastewater treatment and food industry. The conversion involves several methods such as alkaline nitrobenzene, pyrolysis, catalytic technology, combustion, gasification, hydrocracking and oxidation.